Association between dental fracture and amalgam restoration: a case-control study - Luana dos Santos SOUZA; Victor RUANO; Rafael Santos ROCHA; Eduardo VARANDA; Taciana Marco Ferraz CANEPPELE; Eduardo BRESCIANI (Journal of Applied Oral Science)
Abstract Objective: To evaluate the possible clinical association between dental fracture and the presence of amalgam restorations, including other restorative treatments in the control group. The potential association of fractures with dental wear facets and the restoration size was also assessed as a secondary objective. Methodology: Patients with fractured teeth restored with silver amalgam or not were included as the case group (n=25). The control group, with non-fractured teeth, was selected after considering the case group aspects, with twice as many patients (n=50) with posterior teeth sound or restored (amalgam, composite resin, or another restorative material). For both groups, the type of restorative material, extension of the restorations, remaining tooth structure, and the presence or absence of wear facets were analyzed. The teeth were impressed with alginate, and from the plaster models, the extent of fractures or restorations was measured by two calibrated examiners with a digital caliper at the cervico-occlusal and bucco-lingual directions. The data were subjected to the Chi-square test (5%) and odds ratio. Results: There was no statistical difference between the presence or absence of amalgam restorations regarding the risk of tooth fracture. Regarding fractures larger than 3.5mm, the chances of failure are 0.53 for amalgam restorations with no statistical differences (p=0.433), and, regarding the presence of wear facets, the odds ratio of failure is 1.357 for amalgam restorations (p=0.65). Conclusion: It can be deduced that, within the conditions of the study, no discernible association exists between dental fractures and the presence of silver amalgam restorations. Clinical Trial Register: (ReBEC) UNT code U1111-1215-7255.